Bibliometric Analysis of Quran Recitation Development in Scopus International Database Publications 1974-2024 - Raden Ayu Halima (Bulletin of Islamic Research, 2025)
This study applies bibliometric analysis to map the development of research on Qur'an recitation in the Scopus database between 1974 and 2024. The methods used include document and network analysis using tools such as R/RStudio, VOSviewer, and Microsoft Excel. The research process begins with a literature review to determine relevant keywords, then uses Boolean operators to identify 104 documents that meet the criteria. The data obtained is analyzed to map publication trends, distribution of authors, countries, institutions, journals, and collaborations between keywords. The results show a significant increase in publications since 2019, with a peak in 2023. Countries such as Indonesia and the United States dominate publications, while the University of Malaya is the institution with the highest contribution. The Journal of Religion and Health and Journal of Qur'anic Studies recorded the highest number of publications. Lead authors such as Babamohamadi H. and Ghorbani R. showed significant influence, with high citation growth. This study suggests the need for stronger global collaboration and application of technology in Qur'an recitation research to improve the quality of learning.